PENERAPAN METODE GRAPHIC ORGANIZER PADA PEMBELAJARAN BAHASA INDONESIA SISWA KELAS V SD NEGERI 06 BATHIN SOLAPAN - Ayang Ani (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
The basic problem for students today is the low learning outcomes of students who have not achieved the completeness set by the government in the field of education. As found by researchers at SDN 06 Bathin Solapan, the low yield of class V Indonesian language learning. The research method used is classroom action research aimed at improving and improving the learning process in the classroom, classroom action research is an action research carried out with the aim of improving the quality of classroom learning practices. Data increases the analysis of observation of teacher activity at the first meeting by 58% with sufficient categories, at the second meeting of 70% in the good category, then at the third meeting amounting to 82% with a very good category, and at the IV meeting 95% with very good category. the increasing data on the observation of student activities at the first meeting was 60% with sufficient categories, at the second meeting 71% in the good category, then at the third meeting 86% with the very good category, and at the IV meeting 94% with the category very good. Data on the improvement of student learning outcomes, namely the daily test I of 83 and the second daily test of 90.By looking at the various data above, we can conclude that the application of the graphic organizer learning method can improve Indonesian language learning outcomes of fifth grade students of SDN 06 Bathin Solapan.